2008
DOI: 10.1038/ajh.2008.237
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ovariectomy on Blood Pressure and Venous Tone in Female Spontaneously Hypertensive Rats

Abstract: Endogenous ovarian hormones effect a small reduction in MCFP. This effect does not appear to be mediated by adrenergic mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
5
4
1
Order By: Relevance
“…However, we observed that ovariectomy did not further affect blood pressure levels in female hypertensive rats. Our findings are consistent with those of some studies that showed that hypertension was not exacerbated in hypertensive rats after ovariectomy [32,33]. Indeed, menopause is characterized by increases in blood pressure [1].…”
Section: Discussionsupporting
confidence: 93%
“…However, we observed that ovariectomy did not further affect blood pressure levels in female hypertensive rats. Our findings are consistent with those of some studies that showed that hypertension was not exacerbated in hypertensive rats after ovariectomy [32,33]. Indeed, menopause is characterized by increases in blood pressure [1].…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, hypertension is a major risk for diastolic dysfunction and left ventricular hypertrophy and it is a common correlate to heart failure with preserved ejection (Kane et al, ; Lalande & Johnson, ), particularly among aging women (Katholi & Couri, ; Redfield, Jacobsen, Borlaug, Rodeheffer, & Kass, ). Importantly, and consistent with others, BPs over the course of the study in both strains were not affected by OVX (Martin, Redetzke, Vogel, Mark, & Eyster, ; Reckelhoff, ). Consistent with our previous study, worsening of diastolic function, defined by reductions in e′ and increases E/e′, was observed in WKY rats while LV hypertrophy (Wang, da Silva, et al, ), expressed by increases in LV mass, was apparent in both rat strains after OVX.…”
Section: Discussionsupporting
confidence: 89%
“…Since all anesthetics, including isoflurane(37), may influence vascular reactivity, we decided to measure blood pressure under the same conditions as the vascular responses, namely under the influence of isoflurane. However, it is equally important to note that the pattern of blood pressure in the sham operated and gonadectomized SHR is similar to that which we (7, 8, 11, 12, 38) and others (e.g.,(36, 39, 40)) have reported previously. Thus, we are reasonably confident that the blood pressures reported in this study accurately reflect the blood pressure responses to gonadectomy.…”
Section: Discussionsupporting
confidence: 86%
“…For example, some studies reported that estrogen attenuated hypertension development in the spontaneously hypertensive rat (SHR) (5, 6). In contrast other data, including our own, showed that ovariectomy did not raise blood pressure in female SHR (3, 4, 7, 8) when blood pressure was measured relatively soon (3-8 weeks) after ovariectomy. On the other hand, natural estrogen loss induces a slow increase in arterial blood pressure that is only fully expressed in older rats (9).…”
Section: Introductioncontrasting
confidence: 86%